The distribution and ecological factors of aerial algae inhabiting stoneworks in Korea - Song, Mi-Ae; Kim, Ok-Jin; Lee, Ok-Min (Algae (Korean Phycological Society), 2012)
The physico-chemical and environmental factors of stoneworks were examined from March 2009 to October 2010, and aerial algae living on 24 stoneworks in Korea were identified. Fifty aerial algae were found in 24 stoneworks. Of the 50 taxa, 30 taxa were cyanophytes, 16 taxa were bacillariophytes, 3 taxa were chlorophytes, and 1 taxon was a xanthophyte. Nine species, including Aphanocapsa rivularis, which is known to only live in aquatic conditions, inhabited both aquatic and aerial environments. Synechococcus aeruginosus, Scytonema coactile var. thermalis, S. coactile var. minor, Stigonema ocellatum f. ocellatum, and Oscillatoria boryana were newly recorded in Korea. As a result of a correlation analysis between algae and the physico-chemical and ecological environmental factors, the taxa were divided into the bryophyte group, the humidity group, and the dry group. Although the bryophyte group was included within the humidity group, it was separated from the dry group. Taxa in the bryophyte group including Nostoc commune which was distributed in more humid areas than those in the humidity group. However, dry group taxa including Chroococcus pallidus were distributed in lower humidity than that of the two other groups. Correlations among other environmental factors were tested to identify other factors that could substitute for humidity and light intensity. As a result, tree distance, water distance, and plant coverage were replaceable environmental factors. [PUBLICATION ABSTRACT]